Eksploitasi dan Perjuangan Perempuan dalam Novel Re: dan Perempuan Karya Maman Suherman (Kajian Feminisme Sosialis): Penelitian - Sitti Nursamsia; Rachmi Masie, Sitti; Ode Irawati, Wa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The objectives of this study are 1) To describe the forms of exploitation of women in the novel Re: and Women by Maman Suherman (A Study of Socialist Feminism). 2) To describe women's struggle against exploitation in the novel Re: and Perempuan by Maman Suherman (Socialist Feminism Study). The method used in this study is a descriptive method with a qualitative approach. The data collection technique in this study was carried out by reading, taking notes, then identifying the data found, and the final step was to collect the data for analysis. The data in this study refers to facts, information, or descriptions used to analyze existing symptoms or problems. In this study, the data found by the researcher includes all quotations in the novel, whether in the form of words, phrases, sentences, or paragraphs, related to exploitation and women's struggles in the novel Re: and Perempuan by Maman Suherman using a socialist feminist study. The data source comes from the novel Re: and Perempuan by Maman Suherman. The results of the study show that in “Exploitation and Struggle of Women in the Novel Re: and Perempuan by Maman Suherman (Socialist Feminism Study),” there are three forms of exploitation of women, namely sexual, physical, and emotional/psychological exploitation.